Bone marrow cellularity at day 14 is the most important predictive factor for response in patients with AML who require double‐induction chemotherapy: Analysis from a large, single institution experience. Issue 3 (3rd February 2017) - Griffin, Patrick T.; Komrokji, Rami S.; Sweet, Kendra; Al Ali, Najla H.; Padron, Eric; Kubal, Timothy E.; List, Alan F.; Lancet, Jeffrey E.
Abstract: In patients with acute myeloid leukemia (AML), the presence of residual disease at day 14 after primary induction therapy warrants consideration of a second induction cycle. However, data to guide retreatment decisions in such patients are presently limited. Here, we retrospectively reviewed data from 176 patients with AML treated at our institution with a second induction chemotherapy regimen because of day 14 residual disease. Clinical variables and nadir bone marrow features were assessed for correlations with complete remission (CR) and overall survival (OS). In our patient group, 59% achieved CR after a second induction course. Median OS for the entire group was 12.40 months (95% CI, 9.90‐14.90) but 19.07 months (95% CI, 13.13‐25.01) for those who attained a CR. Nadir marrow hypocellularity ( P  < 0.001) at day 14, absolute blast reduction of >50% ( P  = 0.030), and de novo disease status ( P  = 0.018) were significantly correlated with CR achievement after re‐induction. Marrow hypocellularity at day 14 was the most significant predictor of CR on multivariate analysis ( P  < 0.001). Nadir marrow features did not independently correlate with OS when accounting for CR status. Re‐induction was successful in achieving CR in most patients. Study patients who did not achieve CR were more likely to have nonhypocellular marrows.